ANALISIS KERAPATAN MANGROVE SEBAGAI SALAH SATU INDIKATOR EKOWISATA DI PERAIRAN PANTAI DUSUN ALARIANO KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Elsye M Nanulaitta; Abraham H Tulalessy; Deli Wakano (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
This study aims to determine the type and density of mangroves on the coast of Alariano sub-village Amahai District, Central Maluku Regency. This research was carried out in May 2019. The research location was divided into 2 stations. this research is descriptive quantitative. The method used in this research is line transect and sample plot (Transect line plot. Based on the results of the study found 6 types of mangroves including Achantus ebracteatus, Aegiceras corniculatum, Sonnerattia alba, Bruguiera gymnorhiza, Rhizophora apiculata, Xylocarpus granatum. According to the standard criteria of mangrove damage. the results of the calculation of species density at station I and station II are categorized as very dense so that they can be potential for ecotourism development.